Immunomodulatory Properties of Thalidomide Analogs: Pomalidomide and Lenalidomide, Experimental and Therapeutic Applications - Bodera, Pawel; Stankiewicz, Wanda (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2011)
Thalidomide has a broad spectrum of anti-cancer activity. Antitumor activity of thalidomide may be related to a number of known properties, including anti-tumor necrosis factor (TNF)-α and T-cell costimulatory and antiangiogenic activities. The therapeutic potential of thalidomide provided motivation to develop more effective derivatives with considerably reduced toxicity. Thalidomide's immunomodulatory (IMiDs) analogs (lenalidomide, CC-5013; CC-4047, ACTIMID) represent a novel class of compounds with numerous effects on the immune system. Some of these analogs are thought to mediate the anticancer and anti-inflammatory effects observed in humans. Thalidomide is currently approved for the treatment of dermal reaction to leprosy and is currently in phase III trials for multiple myeloma (MM). IMiDs inhibit the cytokine's tumor necrosis factor-α (TNF-α), interleukins (IL) 1β, 6, 12, and granulocyte macrophage-colony stimulating factor (GM-CSF). The repression of the tumor necrosis factor-a (TNF-a) expression is the crucial factor of many of the anti-inflammatory properties of thalidomide. The mechanisms underlying many of the anti-inflammatory properties of thalidomide, including its ability to co-stimulate T cells, still remain unclear. Some recent patent are also summarized in this review.
Keywords: teratogenicity